A Test of the Reproducibility of the Clustering of Cultural Variables. (February 2021) - Fog, Agner
Cultural variables from many different cross-cultural studies can be divided into two clusters of variables that are strongly correlated within each cluster. This is reflected in two factors that are found to be reproduced by independent sets of cultural variables and also reflected in several different cross-cultural studies. The first factor, called superfactor, reflects the combined effects of development and modernization, together with social-psychological effects such as collectivism, conservatism, regality, and tightness. The second factor, called East Asian factor, combines several effects related to East Asian cultures, and possibly also differences in response style. These two factors can be found in several previously published cultural maps, but rotated differently. The common practice of factor rotation has obscured similarities between many different cross-cultural studies. Many previously published cultural factors with different names are in fact differently rotated solutions reflecting the same or closely related underlying cultural differences.